The burden of human coronavirus infection in children hospitalized with severe lower respiratory tract infection in Cape Town, South Africa (2012-2013) - Aliyu, Abdulmumuni Samuel (Department of Paediatrics and Child Health, 2022)
Introduction: In order to better understand the epidemiology and burden of human coronaviruses - NL63, HKU1, OC43 and 229E in South Africa, their role in the aetiology of childhood pneumonia needs to be described. Methods: We used data collected between September 2012 – September 2013 from children aged < 13 years with lower respiratory illness at Red Cross War Memorial Children's Hospital. Respiratory samples including a nasopharyngeal swab (NP) and induced sputum (IS) were taken and tested for the four strains of coronaviruses using FTD33 multiplex realtime PCR. Results: A total of 460 respiratory samples were analysed. Of these, 258 (56.0%) were male and 19 (4.1%) HIV infected. The median age of the children was 8 (IQR 4-18) months. Nasopharyngeal (NP) samples were obtained from 460 children while induced sputum (IS) was not available for six children due to sample loss prior to analysis, leaving 454 available for analysis. A total of 42 (9.1%, 95% CI 6.7- 12.1%) participants tested positive for HCoV in at least one of the two specimens. PCR was able to detect a total of 35 (7.7%) cases from the 454 tested IS specimens compared to 23 (5.0%) detected out of 460 NP samples. The commonest detected HCoVs were coronavirus OC43 with 20 (4.3%) detected from either specimen followed by coronavirus NL63 or coronavirus HKU detected in 14 (3.0%) and 10 (2.2%) of positive test samples, respectively. The least common virus detected HCoV was coronavirus 229E detected in both positive test samples of one participant. Overall HCoVs were detected in 23 (8.9%) of boys compared to 19 (9.1%) of the girls who returned a positive test; p=0.856. The overall age distribution of children with PCR detected HCoVs was similar to that of children with a negative result with median age of 10 (IQR 5- 16) months and median of 8 (IQR 4- 19) months, respectively; p=0.535. Prevalence of HCoV was 11/192 (5.7%), 23/153 (15.0%) and 8/115 (7.0%) in children <6 months old, 6-18 months and over 18 months respectively; p=0.008. Conclusion: Children aged 6 to 18 months had double the risk of other age groups.